Comparative Proteomic Analysis of Sweet Orange Petiole Provides Insights Into the Development of Huanglongbing Symptoms - Li, Bo; Zhang, Yi; Qiu, Dewen; Francis, Frédéric; Wang, Shuangchao (Frontiers in Plant Science, 2021)
Huanglongbing (HLB) is the most destructive citrus disease worldwide. This is associated with the phloem-limited bacterium Candidatus Liberibacter, and the typical symptom is leaf blotchy mottle. To better understand the biological processes involved in the establishment of HLB disease symptoms, a time-course proteomics analysis was performed to reveal the global protein accumulation profiles in leaf petiole, where Ca. L. asiaticus (CLas) prefer to colonize and amass, of CLas-infected Newhall sweet orange (Citrus sinensis) plants at the asymptomatic and symptomatic stages compared to healthy counterpart. Photosynthesis, especially the pathway involved in the photosystem I and II light reactions, was shown to be suppressed throughout the whole CLas infection cycle. Also, starch biosynthesis was induced after the symptom-free prodromal period. Many defense-associated proteins were more extensively regulated in the petiole with the symptoms than the ones from healthy plants. The change of salicylic and jasmonic acid levels in different disease stages had a positive correlation with the abundance of phytohormone biosynthesis-related proteins. Moreover, the protein-protein interaction network analysis indicated that a F-type ATPase and an alpha-1,4 glucan phosphorylase were the core nodes in the interactions of differentially accumulated proteins. Our study indicated that the infected citrus plants probably activated the non-unified and lagging enhancement of defense responses against CLas at the expense of photosynthesis, and contribute to find out the key CLas-responsive genes for tolerance and resistance breeding.